Orientasi Kewirausahaan Dan Inovasi Dalam Meningkatkan Kinerja Pemasaran Di Masa Pandemi Covid-19 - Maria Ulpah; Erry Sunarya; Asep Muhamad Ramdan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of entrepreneurial orientation and innovation variables on marketing performance. This study uses quantitative methods. The population in this study is the owner of MSME cake in the city of Sukabumi and the sample used is 36 respondents. The data analysis technique used is multiple linear regression analysis and the sample technique used is probability sampling. The results of this study indicate that simultaneously and partially the variables of entrepreneurial orientation and innovation have a positive and significant influence on marketing performance. The results of the f test, which is known from the value of Fcount 44,229 > 3.28, shows that the value of Fcount is greater than Ftable and from the correlation results in this study, it has a very strong and high value of 0.737. Meanwhile, from the results of the t-test value, namely Tcount 3,555 > 1,692, it shows that Tcount is greater than Ttable, so it can be concluded that the entrepreneurial orientation and innovation variables have an influence on marketing performance. Keywords: Entrepreneurship orientation, Innovation, Marketing Performance